Existence Results for a Nonlinear Semipositone Telegraph System with Repulsive Weak Singular Forces. (27th December 2011) - Wang, Fanglei; Wang, Yunhai; An, Yukun
Abstract : Using the fixed point theorem of cone expansion/compression, we consider the existence results of positive solutions for a nonlinear semipositone telegraph system with repulsive weak singular forces.